Age at first parturition, parturition intervals, and milk production in saanen, marota and crossbred goat's - Cancio, Carlos Roberto Braga; de Castro, Roberto Soares; Coelho, Lia de Alencar; Rangel, José Henrique de Albuquerque; de Oliveira, José Cícero (Pesquisa Agropecuaria Brasileira, 1992)
Aiming at evaluating the productive and reproductive performance of Saanen and of Marota goats and of crossbred Saanen x Marota in the semi-arid region of Alagoas, Brazil, the age at first parturition, the interval between parturitions, and milk production of goats raised at the Santana do Ipanema Experiment Station in Alagoas, Brazil, were studied. The management method used was the local one; i.e., the semi-extensive, with controlled natural cross breeding. The milk control was made twice a week during 168 days of lactation (1986-1987). The age at first parturition of Saanen (824±156 days) was bigger than that of the crossbreed (650±157 days), and the interval between parturitions was the same in both breeds (367±21 days). The total production average and daily milk of Saanen goats (178 and 1.06±0.34 kg) and that of the crossbred (201 and 1.20±0.29 kg) were similar, but were higher than for Marota (66 and 0.39±0.08 kg). Ayalising the tendency of the lactation curves, a gradatively/decreasing milk production with some oscillation was observed.
Keywords: goats; goat reproduction; goat milk production